Introduction - Daly, Paul (Apex Courts and the Common Law, 2019)
The overarching theme of this collection is the influence of apex courts on the development of the common law¹ – in particular, how the institutional position of apex courts causes them to shape the common law and, conversely, how the traditions of the common law shape the way in which apex courts conceive of their role. Contributors from around the common law world address the overarching theme in three different contexts: first, the particular characteristics of the apex courts of several selected jurisdictions; second, the influence, if any, of constitutionalism and bills of rights on apex courts’ relationships to the
Num Pages: 3-